1993
DOI: 10.1037/h0089381
|View full text |Cite
|
Sign up to set email alerts
|

Play therapy for multicultural populations: Guidelines for mental health professionals.

Abstract: This article describes methods and techniques of play therapy for use with multicultural and diverse populations. Barriers to counseling multicultural children and Eurocentric play therapy techniques with multicultural populations are highlighted. Specific guidelines and examples for play therapy with multicultural children are provided. Recommendations and implications for mental health professionals are discussed.The alternative perspectives of children from differing racial and ethnic backgrounds present a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 19 publications
0
23
0
Order By: Relevance
“…Although research suggests differences in children across cultures regarding their emotions and behaviors (Chen & Eisenberg, 2012), little has been published on multicultural issues specifically in play therapy. Issues of multicultural differences are a regular component of play therapy (Coleman, Parmer, & Barker, 1993). Self-awareness regarding cultural beliefs and values in addition to a dedication to the field of play therapy will only help further This document is copyrighted by the American Psychological Association or one of its allied publishers.…”
Section: Multicultural Considerations Related To Work With Childrenmentioning
confidence: 99%
See 1 more Smart Citation
“…Although research suggests differences in children across cultures regarding their emotions and behaviors (Chen & Eisenberg, 2012), little has been published on multicultural issues specifically in play therapy. Issues of multicultural differences are a regular component of play therapy (Coleman, Parmer, & Barker, 1993). Self-awareness regarding cultural beliefs and values in addition to a dedication to the field of play therapy will only help further This document is copyrighted by the American Psychological Association or one of its allied publishers.…”
Section: Multicultural Considerations Related To Work With Childrenmentioning
confidence: 99%
“…Though Coleman et al (1993) identified guidelines for working with children from diverse populations; few publications address multicultural competencies necessary for the training of developing play therapists (Ritter & Chang, 2002). Penn and Post (2012) conducted a national survey of 510 APT members investigating their self-reported multicultural competencies.…”
Section: Multicultural Considerations In the Structure Of Graduate Pl...mentioning
confidence: 99%
“…These guidelines operationalize the previously presented concepts of awareness, scientific minded-ness, dynamic sizing, and culture-specific knowledge. The following suggestions were synthesized from several sources including the Association for Advanced Training in the Behavioral Sciences (1988), Coleman et al (1993), and Paniagua (1994) and Vraniak and Pickett (1993) as each was summarized in Thomas and Cobb (1999). Suggestions on how teachers can respect children's home languages and cultures made by Garcia (2003) were also incorporated.…”
Section: Suggestions For Culturally Competent Practicementioning
confidence: 99%
“…The child and parents on the other hand may be quite satisfied with a spiritual explanation that attributes the behavior to the child being of “two minds” and existing comfortably between traditional male and female thinking and roles. Further, North American First Peoples emphasize the here and now; “time-consciousness does not go by the clock in traditional Native American Culture … the right time occurs when one is ready” (Axelson, 1993, p. 71, as quoted in Coleman, Parmer, & Barker, 1993).…”
Section: Existing Problemsmentioning
confidence: 99%
See 1 more Smart Citation